Management of advanced breast cancer with the epothilone B analog, ixabepilone - William Gradishar (Dove Medical Press, 2009)
William GradisharRobert H Lurie Comprehensive Cancer Center, Northwestern University Feinberg School of Medicine, Chicago, IL, USAAbstract: Despite the activity of standard chemotherapies in advanced breast cancer, disease progression remains inevitable. Most patients exposed to anthracyclines and taxanes develop resistance and a significant subset shows primary resistance. The increasing use of these agents as adjuvant therapy may result in more anthracycline- and taxane-resistant patients in the metastatic setting; few treatment options are available for patients with metastatic breast cancer (MBC) resistant to multiple chemotherapies. The heterogeneity of breast cancer represents another therapeutic challenge. Breast cancers may be classified as luminal, human epidermal growth factor 2 (HER2)-positive, or estrogen receptor-, progesterone receptor-, and human epidermal growth factor 2-negative (ER/PR/HER2-negative, triple negative). HER2-positive and ER/PR/HER2-negative tumors are associated with poor prognosis owing to aggressive disease and poor long-term response to therapy. The epothilone B analog ixabepilone has low susceptibility to multiple mechanisms of resistance and has demonstrated activity in patients with MBC resistant to anthracyclines, taxanes, and/or capecitabine. Ixabepilone is the first epothilone to be approved, as monotherapy or in combination with capecitabine, for treatment of resistant/refractory MBC or locally advanced breast cancer. Treatment with ixabepilone is an option for patients with ER/PR/HER2-negative or HER2-positive disease and/or primary resistance to taxanes.Keywords: breast cancer, drug resistance, epothilone, HER2-positive, ixabepilone, ER/PR/HER2-negative (triple negative)